Impact of Wedge Effect on Outcomes of Intertrochanteric Fractures Treated with Intramedullary Proximal Femoral Nail - Shen-Ho Yen (MDPI AG, 2021)
The purpose of this study is to investigate the risk factors for wedge effect and its relevance between blade cut-out in patients with intertrochanteric fractures (ITF) treated with proximal femoral nail antirotation II (PFNA-II). A total of 113 patients with ITF treated with PFNA-II between 2012 and 2016 were retrospectively analyzed. Radiographic variables including preoperative fracture pattern, fracture classification, lateral wall fracture, and postoperative neck–shaft angle (NSA), femoral offset (FO), blade cut-out, and Parker’s ratio were measured for analysis. An average of 4.16° of varus malalignment in NSA and 5.5 mm of femoral shaft lateralization in FO was found post-operatively. The presence of lateral wall fracture was significantly related to post-operative varus change of NSA (p < 0.05). After at least one year of follow up, the blade cut-out rate was 2.65% (3/113), and Parker’s ratio was significantly higher in patients with blade cut-out (p = 0.0118). This study concluded that patients with ITF-present preoperative lateral wall fracture and postoperative higher Parker’s ratio in AP radiography showed higher incidence of wedge effect that might increase risk of blade cut out.